Seroprevalence and Risk Factors of Toxocara canis Infection in Children (2–15 Years Old) Referred to Health Centers of Lorestan Province, Iran - Mahmoudvand, Hossein; Taee, Nadereh; Ebrahimzadeh, Farzad; Mirhosseini, Mojgan Sadat; Faraji, Mojgan (Journal of Pediatric Infectious Diseases, 2018)
This study aims to evaluate the seroprevalence and risk factors for Toxocara canis infection in children (2–15 years old) referred to health centers of Lorestan province, Iran. This cross-sectional study was performed from August 2016 to March 2017 on 316 children. All serum samples were tested using the commercially available anti IgG-Toxocara kit (IBL, Germany) according to manufacturer's instructions. Of the 316 children, 14 (4.4%) tested seropositive for anti-T.canis IgG antibody. The variables used to evaluate association between risk factors and status of anti-T. canis IgG antibodies were age, gender, area of residence, eosinophilia, contact with dogs, and consumption of raw or unwashed vegetables and fruits. Risk factors that were significantly related to T. canis seropositivity included living in rural regions (p = 0.018) and contact with dogs (p = 0.001). However, other demographic and risk factors did not demonstrate any association with T. canis seropositivity. To conclude, we found that T. canis infection is prevalent among children (2–15 years old) referred to health centers of Lorestan province, Iran with an overall seroprevalence rate of 4.4%. These findings may be a warning for health centers to pay special attention to toxocariasis among children (2–15 years old) and design screening programs for its prevention.
Keywords: toxocariasis; ELISA; IgG; Lorestan